Experimental Study on Cracking Behavior and Mechanism in Desiccating Soils in Xi’an, Shaanxi Province, China - Xin Wei; Chongyang Gao; Dongdong Yan; Ke Liu (Advances in Civil Engineering)
Drying-induced cracks are frequently observed in soils, which can severely influence the mechanical parameters of soils in geotechnical engineering applications. In addition, geohazards can also be accelerated with the formation of preferential path in slopes caused by cracks in soils. This study aims to analyze the cracking behaviors and mechanisms of a special soil collected in northwestern China using experimental methods. Local displacements and strains can be obtained and analyzed with Digital Image Correlation (DIC) method. Combined with DIC method, the tensors maps with total “mechanical” principal strain are drawn. Cracks in mixed opening-sliding mode are identified and the curling phenomenon of soils is observed in situ. Three typical types of crack patterns are observed, which are “T,” “Y,” and “wave-ring,” respectively. Crack pattern of “T” is more frequent than the other two types. The identification of cracking behaviors and mechanisms is helpful for the analysis of mechanical properties of soils and the prevention of geohazards in northwestern China.